Wireless communication architectures based on data aggregation for internal monitoring of large-scale wind turbines. (August 2016) - Ahmed, Mohamed A.; Kim, Young-Chon
Wireless networks are regarded as a promising candidate for condition monitoring systems of large-scale wind turbines due to the design flexibility, easy deployment, and reduced installation cost. This article investigates different data aggregation approaches of wireless-based architectures for the internal monitoring of a large-scale wind turbine. The main objective is to construct a wireless internal network inside the wind turbine nacelle, for collecting sensing data from different parts and transmitting the data to a remote control center through a wireless external network that serves the turbine towers of the wind farm. The proposed wireless network architectures consist of wireless sensor nodes, coordinator nodes, and a front-end device. The designs of the wireless-based architectures involve choices of physical components, sensor types, sampling rate, and data rate. Wi-Fi is a promising technology that is considered for the wind turbine internal network in this work. Through simulations, the network performance is evaluated with regard to end-to-end delay for different data aggregation approaches of wireless-based architectures.